2014
DOI: 10.1097/meg.0000000000000094
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and clinical response to Saccharomyces boulardii therapy in diarrhea-dominant irritable bowel syndrome

Abstract: S. boulardii with ispaghula husk was superior to placebo with ispaghula husk in improving the cytokine profile, histology, and quality of life of patients with IBS-D. These preliminary results need to be confirmed in a well-powered trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 27 publications
3
61
0
7
Order By: Relevance
“…Similarly, the range of included IBS patients ranged from 12 to 362. Two trials included IBS-C 99,101 and 3 trials only IBS-D patients, 84,96,97 while 2 studies stratified the patients into IBS-C and IBS-D 85 or into IBS-D and IBS-M. 95 Only one study addressed another subgroup of patients who may benefit from probiotics: patients with post-infectious IBS. 110 Unfortunately, the researchers did this post-hoc rather than prospectively (see below).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, the range of included IBS patients ranged from 12 to 362. Two trials included IBS-C 99,101 and 3 trials only IBS-D patients, 84,96,97 while 2 studies stratified the patients into IBS-C and IBS-D 85 or into IBS-D and IBS-M. 95 Only one study addressed another subgroup of patients who may benefit from probiotics: patients with post-infectious IBS. 110 Unfortunately, the researchers did this post-hoc rather than prospectively (see below).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Studies that noted an improvement of QoL without changes in abdominal symptoms (pain, stool frequency, and bloating), 84,95,101 were labelled as "negative except QoL," since it is against all recommendations (Rome criteria and FDA/EMA) to use QoL as a primary endpoint in IBS treatment studies. Three more studies were identified as negative, contrary to the evaluation of the respective authors: one found a significant effect on abdominal pain, but not on other IBS symptoms.…”
Section: Global Outcomementioning
confidence: 99%
See 2 more Smart Citations
“…De manera contraria, el estudio de Stevenson y colaboradores en Sudáfrica es poco concluyente y no encuentra diferencias estadísticamente significativas entre el uso de probióticos (Lactobacillus plantarum 299 en dosis 5 x 10 9 UFC/día) y placebo, al igual que el estudio de Ludidi y colaboradores en Holanda con 35 pacientes, Søndergaard y colaboradores en Dinamarca con 52 pacientes y Abbas y colaboradores en Pakistán, que suministraron 750 mg de Saccharomyces boulardii o placebo a 72 pacientes; sin embargo, en este caso se reportó la disminución de citoquinas proinflamatorias (interleuquina 8 y factor de necrosis tumoral [TNF]) en los pacientes suplementados, lo cual traería un beneficio de esta conducta (p=0,001) (23)(24)(25)(26).…”
Section: Síndrome De Intestino Irritableunclassified